Most recent dreams vs. diary dreams: a methodological note - Schredl, Michael (International journal of dream research, 2020)
Dream content analytic studies rely on dream reports that can be obtained via different collection methods, e.g., REM sleep awakenings in the sleep lab, diaries, and eliciting the most recent dream. Whereas differences between lab and home dreams have been documented, systematic research regarding the differences between most recent dreams and diary dreams is scarce. The present analyses compared 169 most recent dreams and 410 diary dreams collected in independent samples with similar background (psychology students). The results clearly indicate that most recent dreams are more bizarre and include more intense negative emotions when compared to diary dreams. More research is warranted to increase the understanding what factors might contribute to the differences between most recent dreams and diary dreams.
Gesehen am 19.10.2020